The Role of Mediators In Resolution of Inheritance Disputes As Reviewed From Supreme Court Regulation Number 3 of 2022 Concerning Mediation Procedures In Court - Ulfanora (Ekasakti Journal of Law and Justice, 2025)
An inheritance dispute is a dispute that arises between heirs egarding the inheritance left by someone who has died. This conflict is often triggered by disagreements regarding the division of assets, the validity of a will, or determining who is entitled to be an heir. This dispute has a high sensitivity because it involves emotional relationships and close family ties. In the context of its resolution, mediation is a very relevant instrument for inheritance disputes because it can maintain good relations between families. The mediation process provides a constructive dialogue space for heirs to express their respective interests openly. Thus, you can find a fair and mutually acceptable solution without having to go through a lengthy court process. This research is a normative legal research (doctrinal research) with a statutory approach, a conceptual approach, and a case approach. According to Prof. Peter Mahmud Marzuki, normative legal research is a process to find a legal rule, legal principles, and legal doctrines to answer the legal issues faced. The results of this study explain that first,Based on Supreme Court Regulation Number 3 of 2022, the role of a mediator in inheritance disputes is extensive. A mediator acts as a neutral facilitator who not only bridges communication but also explores the root causes and hidden interests. Second, the implementation of this role is based on fundamental principles such as neutrality, confidentiality, and voluntary decision-making. Mediators professionally create a conducive environment for fair and equal negotiations. Third, Overall, Supreme Court Regulation 3/2022 emphasizes that mediation is an effective and humane path to resolving inheritance disputes. The mediator's role is key to transforming destructive conflict into an opportunity to improve family relationships. Therefore, utilizing this mediation mechanism is a wise choice for those seeking a fair, swift solution that maintains the integrity of family ties.